Effect of the combination of enamel matrix derivatives and deproteinized bovine bone materials on bone formation in rabbits' calvarial defects - Shahriar Shahriari; Behzad Houshmand; Hamid Razavian; Saber Khazaei; Fatemeh Mashhadi Abbas (Wolters Kluwer Medknow Publications, 2012)
Background: Various types of materials are used in bone regeneration procedures. The aim of this study was to investigate the use of the enamel matrix derivative (EMD), deproteinized bovine bone mineral (Bio-Oss), and a combination of Bio-Oss plus EMD in the treatment of bone defects created in the rabbits' calvaria. Materials and Methods: Twenty New Zealand white rabbits were included in this experimental randomized single blind study. Four equal cranial bone defects (3 × 6 × 0.5 mm 3) were created in frontal and parietal bone and randomly grafted with Bio-Oss (Group 1), EMD (Group 2), EMD + Bio-Oss (Group 3) and one of them was left unfilled to serve as a control group (Group 4). After 2, 4, 8, and 12 weeks the defects were evaluated by using histological and histomorphometric analysis. Data were analyzed by the Bonferroni test using SPSS 13 statistical software. P value <0.05 considered as statistically significant level. Results: Bone formation in the EMD + Bio-Oss group after 2 weeks was diminished when statistically compared to the other groups (P < 0.05). Bone augmentation after 4 weeks from the lowest to the highest were found in groups 1, 3, 2, and 4, respectively, and these differences were statistically significant (P < 0.05). Using EMD with Bio-Oss increased bone formation in the non-critical defects in the rabbit calvaria during 8 and 12 weeks (P < 0.05). Conclusions: Boosting of EMD plus Bio-Oss seems to have synergic effect on bone regeneration in bone defects.